2020
DOI: 10.1002/jms.4627
|View full text |Cite
|
Sign up to set email alerts
|

Method for rapidly discovering active components in Yupingfeng granules by UPLC‐ESI‐Q‐TOF‐MS

Abstract: Yupingfeng granules (YPFG) were isolated from a traditional Chinese medicine (TCM) formulation composed of three herbs (Astragali Radix, Atractylodis Macrocephalae Rhizoma, and Saposhnikoviae Radix). This formulation is used in TCM to tonify qi, and it can help strengthen exterior and reduce sweating. Nevertheless, the active components of YPFG remain unclear. In this study, the chemical constituents of YPFG were systematically characterized by ultra-performance liquid chromatography coupled with electrospray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In recent years, LC-MS technology has been widely used in the analysis of components of TCM, combining the high separation ability of liquid chromatography with the high sensitivity of mass spectrometry [ 47 , 48 ]. Up to now, the only research on the identification of components in Qi-Fu-Yin was based on UPLC-Q-TOF-MS in vitro [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, LC-MS technology has been widely used in the analysis of components of TCM, combining the high separation ability of liquid chromatography with the high sensitivity of mass spectrometry [ 47 , 48 ]. Up to now, the only research on the identification of components in Qi-Fu-Yin was based on UPLC-Q-TOF-MS in vitro [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the cleavage rule of reference standards and reference data from literature [40,41], lactones could easily eliminate the small neutral fragments such as H 2 O (18 Da), CO (28 Da), CO 2 (44 Da), CH 3 (15 Da), MeOH (32 Da), and/or the combination of these fragments. These fragmentation mechanisms concluded the characterization of F I G U R E 6 Characteristic MS/MS spectra and possible fragmentation pathways of chlorogenic acid, 6-gingerol, atractylenolide-III lactones in YWD, and a total of eight lactones including three lactones (labeled as P167, P196, P205), two limonins (labeled as P123, P142), and three coumarins (labeled as P17, P111, P178) were identified in YWD (Table S3).…”
Section: Characterization Of Lactones In Ywdmentioning
confidence: 99%
“…Our group characterized 58 constituents in YPFG and detected 13 metabolites in the plasma of rats administered with YPFG. In addition, it was observed that the enriched flavonoids, chromones, and saponins extract in YPFG could significantly improve rats with immunosuppression and the extract had similar efficacy to YPFG 9 . It has been found that these components may regulate the metabolism of bile acids by enhancing the expression of the Farnesoid X receptor (FXR) and liver X receptor (LXR) to achieve immune regulation by integrating metabolomics and network pharmacology 10 …”
Section: Introductionmentioning
confidence: 99%
“…The current study aimed to develop a method based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) to simultaneously detect and quantify 15 bioactive components (prim‐O‐glucosylcimifugin, calycosin 7‐O‐glucoside, cimifugin, 5‐O‐methylvisammioside, ononin, sec‐O‐glucosylhamaudol, calycosin, astragaloside IV, astragaloside III, formononetin, astragaloside II, isoastragaloside II, cyclocephaloside II, astragaloside I, and isoastragaloside I) (Figure 1) in YPFG. These 15 compounds were prototypes of the metabolites of YPFG in plasma and have been found to have therapeutic effects on immunosuppressive rats induced by cyclophosphamide 9,10 . Furthermore, the content measured by LC–MS/MS was compared with that measured by HPLC, which provided a reference for further research on the material basis of YPFG and the quality evaluation of YPFG and other Yupingfeng preparations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation